PMMA nanoplastics induce gastric epithelial cellular senescence and cGAS-STING-mediated inflammation via ROS overproduction and NHEJ suppression - Xiao Li; Yixing Huang; Dan Zu; Haidong Liu; Hanyi He; Qimei Bao; Yanhua He; Chen Liang; Guoyan Luo; Yaoshu Teng; Yin Shi; Zu Ye; et al. (Ecotoxicology and Environmental Safety)
The increasing environmental presence of nanoplastics (NPs) has raised concerns about their potential impact on biological systems. We investigated the repercussions of polymethyl methacrylate (PMMA) NPs exposure on normal gastric epithelial cells and revealed a pronounced increase in senescence-associated β-galactosidase activity and G1 phase cell cycle arrest. Our study demonstrated a dose-dependent increase in reactive oxygen species (ROS) and DNA damage, underscoring the pivotal role of ROS in PMMA NPs-mediated effects, a novel contribution to the existing body of knowledge dominated by polystyrene particles. Furthermore, we explored the influence of PMMA NPs on DNA damage response mechanisms, highlighting the significant inhibition of nonhomologous end-joining (NHEJ). Our findings help to elucidate the consequent genomic instability, as evidenced by increased chromosomal aberrations and micronuclei formation. By connecting these cellular manifestations to organism-level effects, we hypothesize that PMMA NPs play a critical role in aging processes. Our work revealed an activated cGAS-STING signaling pathway after PMMA NPs exposure, which correlated with aging-related inflammation and behavioral changes in mice. Importantly, our study provides comprehensive evidence of PMMA NPs-induced premature aging in gastric epithelial cells, shedding light on the molecular intricacies underlying DNA damage, repair impairment, and inflammation. Our research prompts heightened caution regarding the risks of NPs exposure and calls for further investigation into the broader implications of these environmental pollutants on aging processes in higher organisms.